2001
DOI: 10.1007/s001250051579
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-dependent control of hepatic glycogen stores in healthy humans

Abstract: Increased endogenous glucose production (EGP) could contribute to fasting hyperglycaemia in Type II (non-insulin-dependent) diabetes mellitus and could result from increased rates of glycogenolysis or gluconeogenesis (GNG) AbstractAims/hypothesis. Non-esterified fatty acids and glycerol could stimulate gluconeogenesis and also contribute to regulating hepatic glycogen stores. We examined their effect on liver glycogen breakdown in humans.Methods. After an overnight fast healthy subjects participated in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 26 publications
1
74
0
Order By: Relevance
“…Increased levels of serum free fatty acids have been implicated as a causative factor in excess HGP in type 2 diabetes (43)(44)(45)(46). IUGR animals used in the present study did not yet exhibit increased serum NEFA levels, suggesting that an alternate mechanism other than one involving fatty acids is responsible for increased glucose production by the liver.…”
Section: Discussionmentioning
confidence: 50%
“…Increased levels of serum free fatty acids have been implicated as a causative factor in excess HGP in type 2 diabetes (43)(44)(45)(46). IUGR animals used in the present study did not yet exhibit increased serum NEFA levels, suggesting that an alternate mechanism other than one involving fatty acids is responsible for increased glucose production by the liver.…”
Section: Discussionmentioning
confidence: 50%
“…In healthy individuals, increased plasma NEFAs have been shown to not only stimulate GNG, but cause compensatory inhibition of glycogenolysis during euglycaemia [32]. Indeed, we and others have previously demonstrated that isolated changes in NEFA levels do not change the rates of EGP during euglycaemia [9,33].…”
Section: Discussionmentioning
confidence: 69%
“…during a glucose load or in type 2 diabetes [4]. Interestingly, the 2 H 2 O and MRS methods yield similar results in healthy humans during fasting [15][16][17] but different results in patients with liver cirrhosis [18] and type 2 diabetes [4], and during NEFA elevation [16,17,19], supporting the idea that glycogen cycling operates differently in diabetes mellitus and certain nutritive conditions.…”
Section: Introductionmentioning
confidence: 90%